School of rock: Datuk M.Nasir and Datuk Ramli Sarip go on a university tour- you're already interested, right? - Begum, Mumtaj (The Star, 2016)
The first time Datuk M.Nasir and Datuk Ramli Sarip did a tour together, it was in 1982 when Nasir's then group Kembara opened for Ramli's popular band Sweet Charity. Since then, the two greats in the Malay music industry have collaborated on many musical projects such as the recent sold out Ramli & Nasir: Brotherhood in Music showcase at Esplanade, Singapore.But, never did they do a full tour together again, Well until now.